The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/atoms9040099
|View full text |Cite
|
Sign up to set email alerts
|

Binary-Encounter Model for Direct Ionization of Molecules by Positron-Impact

Abstract: We introduce two models for the computation of direct ionization cross sections by positron impact over a wide range of collision energies. The models are based on the binary-encounter-Bethe model and take into account an extension of the Wannier theory. The cross sections computed with these models show good agreement with experimental data. The extensions improve the agreement between theory and experiment for collision energies between the first ionization threshold and the peak of the cross section. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The BEB method can also be used to model the direct positron impact ionization of atoms and molecules with the Binary Encounter Dipole (BED) model combined with the Wannier-type threshold law [36] to give a simple analytical formula for ionization [29,30]. The BEB model is the simplified version of the BED [28] model.…”
Section: Binary Encounter Bethe (Beb) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The BEB method can also be used to model the direct positron impact ionization of atoms and molecules with the Binary Encounter Dipole (BED) model combined with the Wannier-type threshold law [36] to give a simple analytical formula for ionization [29,30]. The BEB model is the simplified version of the BED [28] model.…”
Section: Binary Encounter Bethe (Beb) Modelmentioning
confidence: 99%
“…Also, Bartschat et al showed [27] a way to calculate electron impact ionization cross-sections using the R-matrix method for atoms, which is computationally expensive. In this work, we have used the BEB model, where no fitting parameters are used to calculate electron impact TICS, which was originally formulated by Kim et al [28]; for positron impact TICS, we used the various modified BEB models formulated by Fedus et al [29] and Franz et al [30]. In recent years, the BEB method has been very successful in calculating TICS for various molecules ranging from diatomic [31] to organic molecules [32], with applications in plasma and biological sciences.…”
Section: Introductionmentioning
confidence: 99%
“…In this volume, we present a "cross-section" of different approaches, applications and processes, from industrial plasmas [3,4] to molecules of biological interest [5][6][7]; from experiments at ultra-low temperatures [8,9] to processes relevant for thermonuclear synthesis [10]. Thanks to a global response to the invitation, this volume hosts in an equilibrated manner the experimental aspects [6,8,9], ab-initio theories [7,[10][11][12] and semi-empirical approaches [13][14][15][16], both for electron and positron scattering [11,[15][16][17].…”
mentioning
confidence: 99%
“…The ionization of atoms and molecules, at least in the case of electron collisions, has rather vast experimental coverage. This allows us to test different theoretical and semi-empirical approaches, which, in turn, allow us to predict cross sections for species inaccessible for direct measurements, such as highly charged ions [10], molecular metastables [15] or metals [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation